N‐Oxide–N‐oxide interactions and Cl…Cl halogen bonds in pentachloropyridine N‐oxide: the many‐body approach to interactions in the crystal state. Issue 2 (9th January 2018) - Wzgarda-Raj, Kinga; Rybarczyk-Pirek, Agnieszka J.; Wojtulewski, Sławomir; Palusiak, Marcin
Abstract : In the crystal structure of pentachloropyridine N ‐oxide, molecules are linked by C—Cl…Cl halogen bonds into infinite ribbons extending along the crystallographic [100] direction. These molecular aggregates are further stabilized by very short intermolecular N ‐oxide– N ‐oxide interactions into herringbone motifs. Computations based on quantum chemistry methods allowed for a more detailed description of the N ‐oxide– N ‐oxide interactions and Cl…Cl halogen bonds. Abstract : Pentachloropyridine N ‐oxide, C5 Cl5 NO, crystallizes in the monoclinic space group P 21 / c . In the crystal structure, molecules are linked by C—Cl…Cl halogen bonds into infinite ribbons extending along the crystallographic [100] direction. These molecular aggregates are further stabilized by very short intermolecular N ‐oxide– N ‐oxide interactions into herringbone motifs. Computations based on quantum chemistry methods allowed for a more detailed description of the N ‐oxide– N ‐oxide interactions and Cl…Cl halogen bonds. For this purpose, Hirshfeld surface analysis and the many‐body approach to interaction energy were applied.